'Cycles of disadvantage' revisited: young people, families and poverty across generations. (2nd January 2020) - MacDonald, Robert; Shildrick, Tracy; Furlong, Andy
ABSTRACT: One of Andy Furlong's abiding concerns was to show how the problems of working-class youth are often, straightforwardly, the outcome of inequalities in employment opportunities. On rarer occasions, however, this explanation fits less well. Some young people grow up in families where poverty seems more deeply embedded and inherent to those families. Here, old ideas about a cultural 'underclass' can be tempting to politicians and policy makers. Our qualitative research, with 20 families living in extremely deprived U.K. neighbourhoods, showed that neither a simple lack of job opportunities nor 'cultures of worklessness' explained why hardship persisted for them. Our argument is that circumstances which appear to fit with the idea of an inter-generational, cultural 'underclass', in fact, have their provenance in a semi-permanent constellation of external socio-economic pressures bearing on successive generations of families over decades. Examples did include a shared context of declining job opportunities but extended to a contracting and disciplinary Welfare State, punitive criminal justice systems, poor-quality education and the physical decline of working-class neighbourhoods. We take one example – the destructive impact of local drug markets – to uncover the complex, obscure processes that compound the disadvantage faced by working-class young adults and their families over generations.